2012
DOI: 10.1080/02755947.2012.728181
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Aerial–Roving Surveys to Include Counts of Shore‐Based Recreational Fishers from Remotely Operated Cameras: Benefits, Limitations, and Cost Effectiveness

Abstract: Information on shore‐based recreational fishing is essential for the sustainable management of nearshore fish stocks. However, obtaining estimates of catch and effort from such fishing activity can be complex and expensive due to the large spatial scales over which surveys are typically conducted and the fine‐scale temporal resolution that is desired. Complementary surveys are one option for improving the accuracy of estimates. A pilot study was conducted in Perth, Western Australia, from April to June 2010 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 25 publications
5
60
0
Order By: Relevance
“…Additionally, this bias increases as either total effort declines or the proportion of total effort seen by cameras declines due to an increased frequency of zero camera observations (Sunger et al, 2012) and could therefore lead to bias in trends in estimated total effort. Estimates of total effort were the least precise in false zero situations further emphasizing the need for careful consideration of camera placement (Smallwood et al, 2012). This may be addressed by targeting high-use areas, ensuring the view is clear of obstructions or by using multiple cameras to cover a higher proportion of the total fishing area.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, this bias increases as either total effort declines or the proportion of total effort seen by cameras declines due to an increased frequency of zero camera observations (Sunger et al, 2012) and could therefore lead to bias in trends in estimated total effort. Estimates of total effort were the least precise in false zero situations further emphasizing the need for careful consideration of camera placement (Smallwood et al, 2012). This may be addressed by targeting high-use areas, ensuring the view is clear of obstructions or by using multiple cameras to cover a higher proportion of the total fishing area.…”
Section: Discussionmentioning
confidence: 99%
“…The most appropriate use of cameras for fisheries management and monitoring may come when combining this technology with other monitoring methods, such as creel surveys and aerial surveys (Parnell et al, 2010;Smallwood et al, 2012;Steffe et al, 2008). Smallwood et al (2012) demonstrated how cameras can be used to compliment other methods to capture times (e.g., night) when other methods are not feasible.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations